12 women in education - Ventura, Marne (Women who changed the world (12 Story Library (Firm)), 2020)
Showcases twelve female pioneers in education. Briefly describes their lives and work and spotlights facts about their careers. Short essays at the end of the book highlight women whose work in education is relatively unknown. Includes a glossary, resources for further reading, and an index.